2016
DOI: 10.7554/elife.14740
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule inhibitors identify the RAD52-ssDNA interaction as critical for recovery from replication stress and for survival of BRCA2 deficient cells

Abstract: The DNA repair protein RAD52 is an emerging therapeutic target of high importance for BRCA-deficient tumors. Depletion of RAD52 is synthetically lethal with defects in tumor suppressors BRCA1, BRCA2 and PALB2. RAD52 also participates in the recovery of the stalled replication forks. Anticipating that ssDNA binding activity underlies the RAD52 cellular functions, we carried out a high throughput screening campaign to identify compounds that disrupt the RAD52-ssDNA interaction. Lead compounds were confirmed as R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
121
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 71 publications
(132 citation statements)
references
References 78 publications
4
121
0
2
Order By: Relevance
“…This compound, NP-004255 , is a macrocyle ester, consisting of three trihydroxylated phenolic moieties; it is called corilagin , which belongs to a family of secondary plant metabolites called ellagitannins . Importantly, the hit was validated by both NMR WaterLOGSY and the FRET-based method described above, as fully described in Hengel et al ., 2016 (Hengel et al, 2016), as shown in Figure 9. NP-004255 was shown to bind to RAD52, and compete for ssDNA binding.…”
Section: Using Docking and Molecular Dynamics Simulations To Make mentioning
confidence: 84%
See 4 more Smart Citations
“…This compound, NP-004255 , is a macrocyle ester, consisting of three trihydroxylated phenolic moieties; it is called corilagin , which belongs to a family of secondary plant metabolites called ellagitannins . Importantly, the hit was validated by both NMR WaterLOGSY and the FRET-based method described above, as fully described in Hengel et al ., 2016 (Hengel et al, 2016), as shown in Figure 9. NP-004255 was shown to bind to RAD52, and compete for ssDNA binding.…”
Section: Using Docking and Molecular Dynamics Simulations To Make mentioning
confidence: 84%
“…Amazingly, a single natural product was selected for detailed biophysical study, and found to be in the high nM to low μM range (depending on the assay employed). A rational strategy for targeting the RAD52 PNI is, ostensibly, a nightmarish challenge for structure based design, in that only an unliganded crystal structure of RAD52 was available (PDB 1KN0), which suggests an exotic circular continuous ssDNA binding epitope (Hengel et al, 2016, Kagawa et al, 2002), with a patchwork of alternating hydrophobic and hydrophilic regions and complex water networks in the biding groove. Given the uncertainty of PDB 1KN0 representing the liganded conformation of the protein in solution, the lack of any known ligands that bind in this groove and the complex role of water, we sought to build an integrated workflow for PNI inhibitor discovery which capitalized on in vitro HTS initially, followed by computational studies built on a rigorous statistical framework for understanding why certain chemotypes disrupt the RAD52 PNI.…”
Section: The Challenge Of Ligand Discovery and Design Targeting Prmentioning
confidence: 99%
See 3 more Smart Citations